Prokaryotic community diversity, assembly processes, and potential metabolic pathways of a hexanoic acid-producing microbiota constructed from Chinese baijiu fermentation pit mud - Xiaolong Hu; Mingdong Deng; Xinyu Zhang; Yueqi Wang; Wenyou Zhu; Tian Zeng; Wei Zheng; Yaping Wang; Min Gou; Zhaoxiang Wang (Bioresource Technology, 2026)

GLSP ameliorates monocrotaline-induced pulmonary arterial hypertension through inhibition of the PI3K/AKT and MAPK signaling pathways - Yingying Wei; Siying Zuo; Na Deng; Haijun Guo; Liwei You; Yaping Zuo; Yan Wu; Zhangrong Chen; Wei Li; Xiaoyun Si (Journal of Molecular Histology, 2026)

Acupoint hot compress for labor-pain management: a randomized, parallel-group, controlled trial - Fangfang Wang; Leyi Fu; Xinyue Li; Yuqun Pu; Lianqing Gong; Lin Zhou; Lanxiang Fu; Yaping Chen; Mali Chen; Yue Qin; Xiaoying Lyu; Ye Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Multiscale discrete fracture-matrix method for simulating groundwater flow in fractured geological media - Chen Zuo; Lei Ma; Di Gao; Qiankun Luo; Yaping Deng; Jiazhong Qian (Journal of Hydrology, 2026)

Anomalous contaminant transport in fractured porous media: Insight from asynchronous hydraulic changes in fractures and rock matrix - Lei Ma; Di Han; Qiankun Luo; Yaping Deng; Yunhai Fang; Chao Zhang; Jiazhong Qian (Journal of Contaminant Hydrology, 2026)

Grass carp TMEM33 promotes GCRV replication by targeting MAVS for degradation and suppressing host antiviral immune response - Qian Wang; Zichao Peng; Rong Deng; Yongming Li; Zuoyan Zhu; Yaping Wang; Libo He; Jing Lu (Marine Life Science & Technology, 2026)

Heuristic resistance-driven graph approach for preferential flow pathway identification in 3D discrete fracture networks - Lei Ma; Jixian Li; Yaping Deng; Di Han; Haichun Ma; Xuelin Cui; Jiazhong Qian (Journal of Hydrology, 2026)

A graph Fourier Kolmogorov-Arnold Network (G-FourierKAN) and its application to spring discharge simulation - Yaping Yin; Xingchao Deng; Huiqing Hao; Yonghong Hao; Huibin Chang; Tian-Chyi Jim Yeh (Journal of Hydrology, 2026)

Three-dimensional discrete fracture network identification based on deep learning and reversible jump Markov chain Monte Carlo algorithm - Zhenting Sun; Lei Ma; Quan Li; Yaping Deng; Han Qiu; Haichun Ma; Cihai Chen; Yongshuai Yan; Jiazhong Qian (International Journal of Rock Mechanics and Mining Sciences, 2026)

Immunotoxicity and effects of gut microbiota in chicks exposed to low doses of deoxynivalenol and 15-acetyl-deoxynivalenol - Wandi Bu; Xinyao Wu; Zhihang Zhong; Yaping Fang; Shuang Chen; Jun Jiang; Yiqun Deng (Toxicology and Applied Pharmacology, 2025)

Impact of transient flow on bimolecular reactive transport in varying-aperture fractures - Yajing Liu; Jiazhong Qian; Yong Liu; Lei Ma; Yaping Deng; Hailong Chen (Journal of Hydrology, 2025)

Efficient proton exchange membrane water electrolysis by activating “inactive” catalysts - Yaping Pan; Xinlong Zhuang; Kejie Lao; Linrui Wen; Guang Deng; Hailong Wang; Hanchun Wang; Hua Bing Tao; Nanfeng Zheng (Chemical Engineering Journal, 2025)

Self-adapting deflection contact effect for rock fracture deformation - Haichun Ma; Yanan Wang; Yang Xu; Jiazhong Qian; Yaping Deng (Acta Geophysica, 2025)

Deep learning-based inversion framework for fractured media characterization by assimilating hydraulic tomography and thermal tracer tomography data: Numerical and field study - Cihai Chen; Yaping Deng; Jiazhong Qian; Haichun Ma; Lei Ma; Jichun Wu; Hui Wu (Engineering Geology, 2025)

The diurnal variation characteristics of warm season precipitation in Chongqing from 2011 to 2021 - Yingying Zhou; Yan Zhang; Chengzhi Deng; Qu Guo; Yaping Zhang; Yi Liu; Hong Zhang; Tingting Liu; Fan Xia (Theoretical and Applied Climatology, 2025)

Stochastic modeling of discrete fracture network considering spatial pattern and variability of fracture distribution - Di Gao; Lei Ma; Jiazhong Qian; Qiankun Luo; Haichun Ma; Yaping Deng; Xiaosan Yan (Geosciences Journal, 2025)

High lead-tolerant mutant Bacillus tropicus AT31-1 from rhizosphere soil of Pu-erh and its remediation mechanism - Qiang Li; Wenxia Yuan; Xiujuan Deng; Yaping Chen; Limei Li; Lijiao Chen; Raoqiong Che; Wei Huang; Yamin Wu; Chun Wang; Zejun Wang; Miao Zhou; et al. (Bioresource Technology, 2025)

Global patterns of lake microplastic pollution: Insights from regional human development levels - Dan Chen; Ping Wang; Shiqi Liu; Rui Wang; Yaping Wu; A-Xing Zhu; Chunnuan Deng (Science of The Total Environment, 2024)

Influence of dissolved and non-aqueous phase toluene on spectral induced polarization signatures of soils - Yalin Song; Xiaoqing Shi; André Revil; Yaping Deng (Journal of Hazardous Materials, 2024)

Effect of Fe2+-activated persulfate combined with biodegradation in removing gasoline BTX from karst groundwater: A box-column experimental study - Yaping Jiang; Renqian Lu; Yudao Chen; Ritian Deng; Xu Deng (Environmental Science and Pollution Research, 2024)

Effects of pyrite, quartz and sodium sulfite on roasting of a refractory sulfide concentrate and gold, silver, copper leaching during cyanidation - Wei Yang; Qian Wang; Yaping Wang; Tao Long; Sha Deng (Hydrometallurgy, 2024)

Study on the shale fracture geometry influence on nonlinear gas seepage behavior - Peng Zhou; Haichun Ma; Jiazhong Qian; Xianfa Wei; Yaping Deng (Gas Science and Engineering, 2024)

Characterization of discrete fracture networks with deep-learning based hydrogeophysical inversion - Yaping Deng; Xueyuan Kang; Haichun Ma; Jiazhong Qian; Lei Ma; Qiankun Luo (Journal of Hydrology, 2024)

Different ligand functionalized bimetallic (Zr/Ce)UiO-66 as a support for immobilization of phosphotungstic acid with enhanced activity for the esterification of fatty acids - Qiuyun Zhang; Yaping Wu; Xingyue Hong; Zhenying Li; Yanting Lei; Rongfei Yu; Taoli Deng; Yutao Zhang; Peihua Ma (Sustainable Chemistry and Pharmacy, 2024)

Identification of high-permeability and water-rich zones in a fractured karst water source area based on the hydraulic tomography method - Lei Ma; Xiaofan Sun; Jiazhong Qian; Wei Wang; Yaping Deng; Yunhai Fang (Journal of Hydrology, 2024)

Infection of postharvest pear by Penicillium expansum is facilitated by the glycoside hydrolase (eglB) gene - Meiqiu Xu; Esa Abiso Godana; Jingyu Li; Yaping Deng; Yufei Ma; Huiyuan Ya; Hongyin Zhang (International Journal of Food Microbiology, 2024)

Constructing a cross-field scenario system to aware systemic risk: national security as an example - Qing Deng; Mengjiao Yao; Hui Zhang; Feng Yu; Lida Huang; Yaping Ma (Natural Hazards, 2024)

Engineered hydrochar from waste reed straw for peroxymonosulfate activation to degrade quinclorac and improve solanaceae plants growth - Chunxia Ding; Can Ye; Wei Zhu; Guangyong Zeng; Xuemei Yao; Yu Ouyang; Jie Rong; Yaping Tao; Xiangying Liu; Yaocheng Deng (Journal of Environmental Management, 2023)

Superior solar water purification achieved by the excellent photothermal conversion and thermal management of porous plasmonic TiN nanoparticles - Yaping Gao; Xiaojie Zhou; Nuo Fu; Sihua Su; Baopeng Ma; Qifeng Ruan; Di Wu; Nan Zhang; Ziwei Deng; Ruibin Jiang (Chemical Engineering Journal, 2023)

Study on the seepage mechanisms of rock with bifurcation fractures under confining pressure - Haichun Ma; Peichao Feng; Jiazhong Qian; Yaping Deng; Daoxiang Wu (Hydrogeology Journal, 2023)

Synergistic catalytic wet oxidation of ammonia over carbon-supported low-loading Ru/Cu bimetallic catalyst - Donglin Yang; Bingxiao Feng; Yaping Liu; Chaoting Deng; Hengjun Gai; Meng Xiao; Tingting Huang; Quanhong Zhu; Hongbing Song (Journal of Environmental Chemical Engineering, 2023)

Noncovalent co-assembly of aminoglycoside antibiotics@tannic acid nanoparticles for off-the-shelf treatment of pulmonary and cutaneous infections - Guang Yang; Changrong Wang; Yaping Wang; Xiaoqing Liu; Ye Zhang; Ming Xu; Hongzhang Deng; Weiwei Wang (Chemical Engineering Journal, 2023)

Characterization of DNAPL source zones in clay-sand media via joint inversion of DC resistivity, induced polarization and borehole data - Xueyuan Kang; Christopher Power; Amalia Kokkinaki; André Revil; Jichun Wu; Xiaoqing Shi; Yaping Deng (Journal of Contaminant Hydrology, 2023)

Fine lithospheric structure controlling Meso-Cenozoic tectono-magmatism in the South China Block: Inference from a multidisciplinary analysis - Feiyu Zhao; Yanhui Suo; Lijun Liu; Xianzhi Cao; Sanzhong Li; Suhua Jiang; Juzhi Deng; Mengxue Dai; Ying Liu; Yaping Hu; Shuzhong Sheng; Bin Hu (Earth-Science Reviews, 2023)

Highly efficient catalytic degradation of dicamba using Fe3O4/montmorillonite composite: Mechanism and toxicity assessment - Yu Ouyang; Guangyong Zeng; Wei Zhu; Xuemei Yao; Mengyun Yang; Xiuyu Long; Jie Zheng; Yaping Tao; Yaocheng Deng; Chunxia Ding (Process Safety and Environmental Protection, 2023)

Mesoscopic study of seepage characteristics with shear displacement in a single fracture - Peichao Feng; Haichun Ma; Jiazhong Qian; Yaping Deng (Acta Geophysica, 2023)

Numerical evaluation of the suitability of the equivalent porous medium model for characterizing the two-dimensional flow field in a fractured geologic medium - Lei Ma; Di Han; Jiazhong Qian; Di Gao; Haichun Ma; Yaping Deng; Xiaoliang Hou (Hydrogeology Journal, 2023)

Protective effect of Anneslea fragrans ethanolic extract against CCl4-induced liver injury by inhibiting inflammatory response, oxidative stress and apoptosis - Yudan Wang; Xiaocui Deng; Yaping Liu; Yifen Wang; Xiaodong Luo; Tianrui Zhao; Zhengxuan Wang; Guiguang Cheng (Food and Chemical Toxicology, 2023)

Quantification of solute transport in a fracture-matrix system using geoelectrical monitoring - Yongshuai Yan; Jiazhong Qian; Lei Ma; Guizhang Zhao; Yaping Deng; Haoming Zhang; Yunhai Fang; Yong Liu (Journal of Hydrology, 2023)

Multiscale fractures integrated equivalent porous media method for simulating flow and solute transport in fracture-matrix system - Lei Ma; Di Gao; Jiazhong Qian; Di Han; Kun Xing; Haichun Ma; Yaping Deng (Journal of Hydrology, 2023)

Characterizing seasonal recharge between a river and shallow aquifer in a floodplain based on time-lapse electrical resistivity tomography - Yongshuai Yan; Yaping Deng; Lei Ma; Guizhang Zhao; Jiazhong Qian (Hydrogeology Journal, 2023)

Environmental-friendly hydrochar-montmorillonite composite for efficient catalytic degradation of dicamba and alleviating its damage to crops - Chunxia Ding; Guangyong Zeng; Yaping Tao; Xiuyu Long; Daoxin Gong; Nan Zhou; Rongying Zeng; Xiangying Liu; Yaocheng Deng; Mei-E Zhong (Science of The Total Environment, 2023)

Hydrofacies simulation based on transition probability geostatistics using electrical resistivity tomography and borehole data - Lei Ma; Hui Deng; Yongshuai Yan; Yaping Deng; Weidong Zhao; Xiaohui Tan; Jiazhong Qian (Hydrogeology Journal, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Biological monitoring and health assessment of 21 metal(loid)s in children and adolescents in Liuzhou City, Southwest China - Yaping Li; Yu Zhang; Meng Yu; Liqin Hu; Ting Zeng; Ling Liu; Limei Wang; Liangqiong Deng; Xiang Li; Ping Liu; Dingyuan Zeng; Surong Mei (Environmental Science and Pollution Research, 2022)

gga-miR-142-3p negatively regulates Mycoplasma gallisepticum (HS strain)-induced inflammatory cytokine production via the NF-κB and MAPK signaling by targeting TAB2 - Yaping Yang; Yingjie Wang; Mengyun Zou; Ganzhen Deng; Xiuli Peng (Inflammation Research, 2021)

Pandemic threat posed by H3N2 avian influenza virus - Yaping Zhang; Conghui Zhao; Yujie Hou; Yan Chen; Fei Meng; Yichao Zhuang; Liling Liu; Yasuo Suzuki; Jianzhong Shi; Guohua Deng; Hualan Chen (Science China Life Sciences, 2021)

Characterizing temporal behavior of a thermal tracer in porous media by time-lapse electrical resistivity measurements - Ze Yang; Yaping Deng; Jiazhong Qian; Rui Ding; Lei Ma (Hydrogeology Journal, 2021)

Identification of Potential Biomarkers with Diagnostic Value in Pituitary Adenomas Using Prediction Analysis for Microarrays Method - Hu Peng; Yue Deng; Longhao Wang; Yin Cheng; Yaping Xu; Jianchun Liao; Hao Wu (Journal of Molecular Neuroscience, 2019)

MiR-19a mediates the negative regulation of the NF-κB pathway in lipopolysaccharide-induced endometritis by targeting TBK1 - Nannan Yin; Yaping Yang; Xiaoyan Wang; Chao Yang; Xiaofei Ma; Aftab Shaukat; Gan Zhao; Ganzhen Deng (Inflammation Research, 2019)

Delineation of contaminant plume for an inorganic contaminated site using electrical resistivity tomography: comparison with direct-push technique - Qing Liao; Yaping Deng; Xiaoqing Shi; Yuanyuan Sun; Weidong Duan; Jichun Wu (Environmental Monitoring and Assessment, 2018)

Effects of Land Use Change on Phosphorus Levels in Surface Waters—a Case Study of a Watershed Strongly Influenced by Agriculture - Bin Zhou; Yaping Xu; Rolf D. Vogt; Xueqiang Lu; Xuemei Li; Xiaowen Deng; Ang Yue; Liang Zhu (Water, Air, & Soil Pollution, 2016)

Znrg, a novel gene expressed mainly in the developing notochord of zebrafish - Yaping Zhou; Yan Xu; Jianzhen Li; Yao Liu; Zhe Zhang; Fengjiao Deng (Molecular Biology Reports, 2010)